2008
DOI: 10.1002/jhm.323
|View full text |Cite
|
Sign up to set email alerts
|

Clinical consequences of withholding versus administering renin‐angiotensin‐aldosterone system antagonists in the preoperative period

Abstract: BACKGROUND:Hospitalists involved in perioperative care either stop or continue until the day of surgery renin‐angiotensin‐aldosterone system antagonists (either angiotensin‐converting enzyme inhibitors [ACEI] or angiotensin II receptor subtype 1 antagonists [ARA]) in patients who use these agents chronically. This practice variation reflects uncertainty regarding the risks and benefits of either approach.PURPOSE:The purpose of this study was to assess the clinical consequences of preoperatively continuing vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
2
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(67 citation statements)
references
References 15 publications
3
54
2
2
Order By: Relevance
“…8 Notably, the institutional standard of care for these patients was to instruct them to discontinue ACEI/ARA therapy the day of surgery, although the long-term impact of withholding ACEI/ARA therapy vs continuing the therapy on the day of surgery is unknown. 9 In our study, we also found more hypotensive episodes among ACEI/ARA patients also taking a diuretic vs patients on no antihypertensives. Measurement of blood pressure during procedures performed in the beach chair position remains controversial.…”
Section: Discussionsupporting
confidence: 71%
“…8 Notably, the institutional standard of care for these patients was to instruct them to discontinue ACEI/ARA therapy the day of surgery, although the long-term impact of withholding ACEI/ARA therapy vs continuing the therapy on the day of surgery is unknown. 9 In our study, we also found more hypotensive episodes among ACEI/ARA patients also taking a diuretic vs patients on no antihypertensives. Measurement of blood pressure during procedures performed in the beach chair position remains controversial.…”
Section: Discussionsupporting
confidence: 71%
“…Currently there is debate whether to withhold these medications preoperatively. To address this debate, a number of small studies have been conducted to evaluate if patients taking chronic ACEI or ARBs experience hypotension and require more vasopressors than patients taking other antihypertensive medications during general anesthesia 6,7,9 . The major limitation of these studies is their small sample size and a large number of other antihypertensive drugs taken.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,9 Some studies suggest formulating guidelines to withhold ACEI and ARBs preoperatively 5,8,[10][11][12] . However, few studies address the fact that patients with chronic hypertension are often taking multiple antihypertensive medications from different classes, which may interact and confound results, 13 and little data are available on the effect of the number and class of antihypertensive drug on intraoperative hypotension.…”
Section: Introductionmentioning
confidence: 99%
“…Although continuation of ACEIs/ARBs until the day of surgery has been associated with an increased incidence of hypotension, 180 it is in general recommended that all heart-failure medications, such as ACE inhibitors, ARBs, and beta-blockers, be continued and that the patient's haemodynamic status be carefully monitored and give appropriate volume replacement when necessary. In patients considered susceptible to hypotension, transient discontinuation the day before surgery may be considered.…”
Section: Chronic Heart Failurementioning
confidence: 99%